2014
DOI: 10.1002/jmri.24758
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Bi-component T2* analysis of tendon before and during tensile loading, using UTE sequences

Abstract: No significant difference in single- or bi-component results was found after the application of tension to tendons. Results are similar regardless of UTE sequence used for acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 35 publications
4
64
0
Order By: Relevance
“…The UTE sequence used in our study utilized a center-out twisted 3D cone k-space trajectory which has been shown to increase sampling uniformity, decrease undersampling artifact, and provide better SNR performance when compared to traditional 2D and 3D radial UTE sequences 33 . The sequence has had successful applications in sodium imaging 42,43 and ex-vivo Achilles tendon imaging 24 . In our study, the 3D cone UTE sequence provided complete anatomic coverage of the patellar tendon in human subjects at 3.0T with clinically feasible spatial resolutions and scan times and with an SNR of 54.5, which has been shown to be adequate to accurately estimate bi-component T2* parameters from previous literature 28 and the results of our simulation study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The UTE sequence used in our study utilized a center-out twisted 3D cone k-space trajectory which has been shown to increase sampling uniformity, decrease undersampling artifact, and provide better SNR performance when compared to traditional 2D and 3D radial UTE sequences 33 . The sequence has had successful applications in sodium imaging 42,43 and ex-vivo Achilles tendon imaging 24 . In our study, the 3D cone UTE sequence provided complete anatomic coverage of the patellar tendon in human subjects at 3.0T with clinically feasible spatial resolutions and scan times and with an SNR of 54.5, which has been shown to be adequate to accurately estimate bi-component T2* parameters from previous literature 28 and the results of our simulation study.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al detected short and long relaxing water components in histologically normal human cadaveric Achilles tendon with a T2* of 1.8ms and 9.2ms and a fraction of 79.2% and 20.8% respectively 23 . The Authors later reported that bi-component T2* parameters did not change with tensile loading of the Achilles tendon 24 . Jarus et al compared single-component and bi-component T2* analysis of the Achilles tendon in human subjects and found that the bi-component analysis provided greater diagnostic performance for distinguishing between normal and pathologic tendon 25 .…”
Section: Assessment Of Different Fitting Methods For In-vivo Bi-compomentioning
confidence: 98%
See 3 more Smart Citations